2015
DOI: 10.1097/bpo.0000000000000562
|View full text |Cite
|
Sign up to set email alerts
|

Can Subclinical Rickets Cause SCFE? A Prospective, Pilot Study

Abstract: Although obese children are known to have lower levels of vitamin D and a higher prevalence of SCFE, we found no correlation between low vitamin D and the development of SCFE in this subset of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…On the other hand, Arkader et al. ( 2015 ) reported that all patients diagnosed with SCFE between the ages of 9 and 14 years had normal vitamin D levels. In their series of 15 cases with SCFE, Madhuri et al.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Arkader et al. ( 2015 ) reported that all patients diagnosed with SCFE between the ages of 9 and 14 years had normal vitamin D levels. In their series of 15 cases with SCFE, Madhuri et al.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothyroidism has been shown to be one of the predominant laboratory findings 36 . Although some reports point to differences in bone mineralization testing results 38,39 (i.e., vitamin D, calcium, and parathyroid hormone) or renal osteodystrophy as a cause 37 , routine screening with these tests is typically not necessary and may not be discriminative in patients with or without SCFEs 74-76 . Other atypical presentations, including Klinefelter syndrome, have been reported 77 .…”
Section: Diagnosismentioning
confidence: 99%
“…Although some reports point to differences in bone mineralization testing results 38,39 (i.e., vitamin D, calcium, and parathyroid hormone) or renal osteodystrophy as a cause 37 , routine screening with these tests is typically not necessary and may not be discriminative in patients with or without SCFEs [74][75][76] .…”
Section: Differential Diagnosismentioning
confidence: 99%
“…A study of 20 consecutive children from Los Angeles with SCFE and found no vitamin D deficiency, regardless of obesity status. The majority of the children studied were Hispanic (17 of 20), but the time of year when the vitamin D levels were collected was not given (21). In Vellore, India, all children with SCFE had significantly lower vitamin D levels than the controls (22).…”
Section: Scfementioning
confidence: 99%